Optimasi ekstraksi karagenan dari Kappaphycus alvarezii berbantu metode enzim selulase dan gelombang ultrasonik : Optimization of carrageenan extraction from Kappaphycus alvarezii using ultrasonic-assisted cellulase extraction (UACE) - Kumalaningrum, Amalia Nur; Poeloengasih, Crescentiana Dewi; Azhary, Muhammad Fachrul; Sholihah, Ni’matus; Syafitri, Tatia Asnur; Sabillah, Hana; Nusantara, Bangun Garuda; Christyandari, Debora Ayu (Jurnal Pengolahan Hasil Perikanan Indonesia, 2025)
Carrageenan is a high economic value polysaccharide obtained from red algae as a thickener and stabilizer in various industries. The extraction method of carrageenan commonly used in industry involves a hot alkaline process with a long time, which is inefficient and produces a lot of waste. Consequently, we require an extraction method that enhances efficiency and minimizes environmental effects. The goal of this study is to find the best conditions for extracting kappa-carrageenan from K. alvarezii using the UACE method, considering the quality and percentage of yield. The variables observed in this study were solvent and seaweed ratio (20-100 mL/g), cellulase enzyme concentration (2-10%), and ultrasonication time (20-100 min). The pretreated carrageenan from K. alvarezii was extracted at 80-90ºC for 30 min, characterized, and compared with pure carrageenan according to SNI 8391-1:2017. Increasing the solvent:seaweed ratio, enzyme amount, and ultrasonic time can increase the carrageenan yield up to 62%. However, the carrageenan produced has a darker color than commercial carrageenan. Carrageenan has water content, sulfate, viscosity, heavy metal content according to SNI, while ash content and acid insoluble ash exceed SNI and gel strength of carrageenan is still below SNI. Carrageenan still contains the element N, which indicates the impurity of carrageenan. The results of the FTIR spectrum showed that the carrageenan obtained was of the kappa-carrageenan type. Further research is required to determine the effects of UACE as a pretreatment in the extraction of carrageenan. The objective is to identify methods for producing increased quantities and enhancing the quality of carrageenan.